2000
DOI: 10.1142/s0218127400001705
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Synchronization of Coupled Coherence Resonance Oscillators

Abstract: The effect of coherence resonance can change the firing process in noise-driven excitable systems towards rather regular dynamics. This effect provides a mechanism of the generation of stochastic oscillations whose characteristics are controlled by noise intensity. Following this, a noisy excitable system can be considered as a corehence resonance oscillator. For such functional units, we investigate the mutual and forced synchronization in terms of locking of the peak frequencies in the power spectrum and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Noise-induced phase synchronization and noise-enhanced phase synchronization of coupled HH neurons and ML neurons were studied in [149,[151][152][153]. In numerical simulations, the authors in [149] introduced a mismatch into the leakage parameter in the HH model and keep the other parameters identical.…”
Section: Effects Of Noise On Synchronization Of Coupled Neuronsmentioning
confidence: 99%
“…Noise-induced phase synchronization and noise-enhanced phase synchronization of coupled HH neurons and ML neurons were studied in [149,[151][152][153]. In numerical simulations, the authors in [149] introduced a mismatch into the leakage parameter in the HH model and keep the other parameters identical.…”
Section: Effects Of Noise On Synchronization Of Coupled Neuronsmentioning
confidence: 99%
“…It has been shown that the two different schemes of synchronization observed in periodic oscillators apply also to the synchronization of chaotic oscillators [4,5]. We have shown [6] that stochastic oscillators with coherent resonance [7] can be synchronized, and two different schemes of synchronization were again observed [8].…”
mentioning
confidence: 69%
“…In particular, coherence resonance phenomenon shows that noise enhances the temporal regularity of a dynamical system, which was first noticed by Sigeti and Horsthemke [29] and then theoretically analyzed by Pikovsky and Kurths [24]. Since then, a plethora of theoretical and experimental works including coupled coherence resonance oscillators [13,26] and coupled chaotic systems [16,36] has appeared, which is mainly based on analysis of resonance. All of these studies indicate that noise can play a stabilizing role, and has an effect to drive the stochastic system towards rather regular dynamics.…”
Section: Discussionmentioning
confidence: 99%